Impregnation of Bamboo (Gigantochloa Scortechinii) with Phenolic Resin for the Production of Dimensionally Stable Plybamboo - Uyup, Mohd Khairun Anwar (2008)
Low molecular weight phenol formaldehyde (LMwPF) resin was used to enhance the dimensional stability of bamboo strips (Gigantochloa scortechinii). Resin was impregnated into bamboo strips via vacuum process before the strips were converted into plybamboo. The present study was undertaken to develop a process to produce high dimensionally stable plybamboo. The work included evaluation of resin impregnation process, establishment of suitable drying/curing technique and final pressing of phenolic-treated bamboo strips. Evaluation of bonding properties, dimensional stability and mechanical properties of phenolic-treated plybamboo were also conducted. The bamboo strips were taken from basal and middle portions of bamboo culm. To treat the bamboo strips with LMwPF resin, firstly, a vacuum period of 1 hour was applied before the strips were soaked in resin for at least 90 minutes. The samples were later dried in an oven at 60°C for 9 hours. The mean weight percent gain (WPG) and moisture content (MC) of dried phenolic-treated bamboo strips were 14.5% and 7%, respectively. Drying the phenolic-treated bamboo strips for > 9 hours resulted in cupping of the strips. Phenolic-treated strips were then hot pressed for 5, 8, 11, 14 and 17 minutes at 14 kgm-2 and 140°C. Water absorption (WA), thickness swelling (TS) and linear expansion (LE) of the strips decreased when the curing time was extended from 5 minutes to 17 minutes but antishrink efficiency (ASE) increased. The mean value of modulus of rupture (MOR) for untreated strips (177 Nmm-2) was significantly lower than the phenolic-treated strips (224 Nmm-2) after 17 minutes pressing time. However, no significant difference was observed in modulus of elasticity (MOE) and compression parallel to grain. Results showed that the optimum pressing time for phenolic-treated strips was 11 minutes. This work also established an optimum pressing time to produce high dimensionally stable plybamboo. For this, phenolic-treated bamboo strips were glued together edge-to-edge using phenol resorcinol formaldehyde (PRF) resin to produce a veneer. The veneers were then assembled perpendicular to each other to form a 3-ply (12 mm) and 5-ply (20 mm) plybamboo using phenol formaldehyde resin as a binder. The plybamboos were hot pressed at an optimum pressing condition of 140oC (pressure 14 kgm-2) for 22 (3-ply) and 33 (5-ply) minutes. The bonding strength of the plybamboo obtained in this study met the minimum requirement of MS 228-1991. WA, TS, and LE of phenolictreated plybamboo were significantly lower compared to those of untreated plybamboo. The MOR, MOE and compression parallel to grain of the phenolic-treated plybamboo were significantly higher compared to those of untreated plybamboo. For 3-ply, the values were 164 and 127 Nmm-2 for MOR, and 19767 and 16778 Nmm-2 for MOE, and 60 and 41 Nmm-2 for compression parallel to grain, respectively. Similarly, for 5-ply phenolic-treated plybamboo the MOR, MOE and compression parallel to grain of were 38%, 30% and 33% respectively higher than those of untreated plybamboo. Generally, the treatment of bamboo strips with LMwPF resins were found to significantly improve the properties of plybamboo made from them.